In situ micropillar deformation of hydrides in Zircaloy-4. (15th June 2015) - Weekes, H.E.; Vorontsov, V.A.; Dolbnya, I.P.; Plummer, J.D.; Giuliani, F.; Britton, T.B.; Dye, D.
Abstract: Deformation of hydrided Zircaloy-4 has been examined using in situ loading of hydrided micropillars in the scanning electron microscope and using synchrotron X-ray Laue microbeam diffraction. Results suggest that both the matrix and hydride can co-deform, with storage of deformation defects observed within the hydrides, which were twinned. Hydrides placed at the plane of maximum shear stress showed deformation within the hydride packet, whilst packets in other pillars arrested the propagation of shear bands. X-ray Laue peak broadening, prior to deformation, was associated with the precipitation of hydrides, and during deformation plastic rotation and broadening of both the matrix and hydride peaks were observed. Post-mortem TEM of the deformed pillars has indicated a greater density of dislocations associated with the precipitated hydride packets, while the observed broadening of the hydride electron diffraction spots further suggests that plastic strain gradients were induced in the hydrides by compression.